Upper eyelid reconstruction due to scar contracture following major burn injury: A case series - Zakaria, Iskandar; Rizal, Syamsul; Irwansyah, Denny; Chintia Amelia Pratiwi (Surgical Residency Program Syiah Kuala University, 2024)
Background: Upper eyelid contracture is a regular occurrence after severe facial burns. Numerous problems, such as corneal ulcers and exposure keratitis, may result from it. It is difficult for plastic surgeons to operate in this situation to preserve worst-case scenarios and enhance palpebral function. Methods: In this piece, we showcase two instances: (1) Eight months after suffering a chemical burn injury, a 26-year-old male was diagnosed with bilateral superior palpebral contracture with iris prolapse. Both eyes' visual acuity was 6/6 - 1/¥. A 75-year-old female patient was identified as having a corneal ulcer and a contracture on her left upper eyelid. Both eyes' visual acuity was 20/6 - 1/¥. In order to restore the top eyelid in both patients, we undertook a contracture release and a full-thickness skin graft. Results: Evaluation five days after surgery revealed no evidence of graft lysis and that the graft had taken nicely. On the patient graft from the second, we discovered shifting, although new epithelization will take place. Both of the patients had good eyelid looks following restoration. Conclusion: Plastic surgeons should be aware of the seriousness of significant burn injuries to the face. Patients must receive appropriate instruction on the significance of avoiding consequences from eyelid contractures. In this instance, creating the top eyelid via a skin graft and contracture release technique made sense. We acknowledge that one of the limitations of our study is the brief observational period of the patient's conditions.